2019
DOI: 10.1016/j.oneear.2019.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Co-designing Indus Water-Energy-Land Futures

Abstract: The Indus River Basin covers an area of around 1 million square kilometers and connects four countries: Afghanistan, China, India, and Pakistan. More than 300 million people depend to some extent on the basin's water, yet a growing population, increasing food and energy demands, climate change, and shifting monsoon patterns are exerting increasing pressure. Under these pressures, a ''business as usual'' (BAU) approach is no longer sustainable, and decision makers and wider stakeholders are calling for more int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 75 publications
(75 reference statements)
2
28
0
Order By: Relevance
“…(Maier et al, 2016). A number of water resources studies have generated explorative scenarios by considering the impact of plausible changes in atmospheric carbon concentrations (Anghileri et al, 2018; Beh et al, 2014, 2015a, 2015b; Giuliani & Castelletti, 2016; Giuliani et al, 2016; Haasnoot et al, 2012, 2013; Herman & Giuliani, 2018; Huskova et al, 2016; McPhail et al, 2018), as well as plausible changes in regional socioeconomic conditions (Haasnoot et al, 2013; Wada et al, 2019). In contrast, normative scenarios consider conditions that represent interesting outcomes, as is the case with scenario discovery (e.g., Bryant & Lempert, 2010; Groves & Lempert, 2007; Hadka et al, 2015; Kasprzyk et al, 2013; Kwakkel, 2017; Kwakkel, Walker, et al, 2016; Matrosov et al, 2013; Trindade et al, 2017); conditions that result in one decision alternative being preferable to another, as is the case with MORE (Ravalico et al, 2010), POMORE (Ravalico et al, 2009) and decision scaling (e.g., Brown et al, 2012); or conditions under which certain decision alternatives no longer perform adequately, as is the case with adaptive tipping point approaches (e.g., Haasnoot et al, 2013; Kwadijk et al, 2010; Kwakkel et al, 2015; Kwakkel, Haasnoot, et al, 2016; Vervoort et al, 2014; Walker, Haasnoot, et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Maier et al, 2016). A number of water resources studies have generated explorative scenarios by considering the impact of plausible changes in atmospheric carbon concentrations (Anghileri et al, 2018; Beh et al, 2014, 2015a, 2015b; Giuliani & Castelletti, 2016; Giuliani et al, 2016; Haasnoot et al, 2012, 2013; Herman & Giuliani, 2018; Huskova et al, 2016; McPhail et al, 2018), as well as plausible changes in regional socioeconomic conditions (Haasnoot et al, 2013; Wada et al, 2019). In contrast, normative scenarios consider conditions that represent interesting outcomes, as is the case with scenario discovery (e.g., Bryant & Lempert, 2010; Groves & Lempert, 2007; Hadka et al, 2015; Kasprzyk et al, 2013; Kwakkel, 2017; Kwakkel, Walker, et al, 2016; Matrosov et al, 2013; Trindade et al, 2017); conditions that result in one decision alternative being preferable to another, as is the case with MORE (Ravalico et al, 2010), POMORE (Ravalico et al, 2009) and decision scaling (e.g., Brown et al, 2012); or conditions under which certain decision alternatives no longer perform adequately, as is the case with adaptive tipping point approaches (e.g., Haasnoot et al, 2013; Kwadijk et al, 2010; Kwakkel et al, 2015; Kwakkel, Haasnoot, et al, 2016; Vervoort et al, 2014; Walker, Haasnoot, et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…How many scenarios are generated is generally linked to the philosophy that underpins scenario generation. When scenarios correspond to coherent descriptions of alternative hypothetical futures (e.g., van Notten et al, 2005), the number of scenarios considered is generally small (~3–9, see Table S1 in the supporting information), and scenarios are generally identified using some type of human input, such as the use of participatory approaches involving a variety of stakeholders (e.g., Wada et al, 2019). In contrast, when scenarios are designed to represent a broad range of combined changes in future conditions, the number of scenarios considered is generally large (~100–15,000, see Table S1 in the supporting information), and scenarios are generated using numerical modeling and/or sampling‐ or optimization‐based approaches, with minimal stakeholder input (e.g., Culley et al, 2016, 2019; Hadka et al, 2015; Hall et al, 2012; Herman et al, 2014, 2015; Kasprzyk et al, 2013; Kwakkel et al, 2015; Kwakkel, 2017; Kwakkel, Walker, et al, 2016; McPhail et al, 2018; Quinn et al, 2017, 2018; Singh et al, 2015; Trindade et al, 2017; Watson & Kasprzyk, 2017; Weaver et al, 2013; Zeff et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A common method to link different scales in scenarios is to incorporate themes from global scenario archetypes into local scenario development exercises or using higher level scenarios for regional or local assessments (Ash et al, 2010;Biggs et al, 2007). There is an increasing amount of "multiscale" scenario studies, which are a set of linked scenarios constructed at two or more scales (Biggs et al, 2007;Wardropper et al, 2016;Kok et al, 2019;Wada et al, 2019).…”
Section: Scenario Processmentioning
confidence: 99%
“…When the NEST framework was applied to the Indus River basin in Asia it showed that the interlinkages between water and energy have significant policy implications [8]. Both the CLEWs and NEST frameworks are optimization models that choose the optimal development path within the constraints and trade-offs defined in the model structure, and both focus solely on the climate, land, water and energy nexus.…”
Section: Recent Modelling Advancesmentioning
confidence: 99%